FAKTOR PENENTU KEPUTUSAN KONSUMEN INDONESIA MEMILIH TEMPAT BELANJA DISEBUAH E-COMMERCE (Theory of Planned Behavior) - Dede Suleman (Universitas Mercu Buana, 2018)
The development of the world of commerce has changed from conventional to digital, this is the underlying emerging e-commerce industry in the present era which became a bridge for consumers and sellers meet and exchange goods and money. The development of ecommerce is very fast both for local and from outside because triggered by the growth of sales through this media so that competition is very tight. Therefore it is necessary to note what causes consumers to choose shopping in one e-commerce and what are the reasons and what products are sought after. From the results of our research we found that it was associated with the theory of planned behavior (TPB) then it is in that the attitude of perception greatly affect decision-making such as sense of security, reliable and accessible that makes customers decide to choose in one of e-commerce and e -commerce the most popular is Lazada with products that buy Fashion, gadgets and cosmetics. From the above we ex10pect e-commerce continues to pay attention to customer expectations of this research so that the e-commerce is selected as a place of shopping by consumers